Self-channelled high harmonic generation of water window soft x-rays. (3rd August 2018) - Cardin, V; Schmidt, B E; Thiré, N; Beaulieu, S; Wanie, V; Negro, M; Vozzi, C; Tosa, V; Légaré, F
Abstract: Owing to the increasing significance of high harmonic generation (HHG) as a tabletop coherent x-ray source and the coming of age of intense infrared (IR) lasers, the development of high brightness soft x-ray beamlines is gaining a lot of attention. We discuss the self-guided propagation of high energy IR pulses around 1.8 μ m centre wavelength being loosely focused into a long, high-pressure gas cell. A bright x-ray beam with photon energies extending up to the oxygen K-edge at 543 eV is achieved with a flux of 2.9 × 10 3 photons/shot/1% bandwidth around the carbon K-edge (280 eV). We provide experimental and numerical evidence of an ionization steady state condition in the generation medium causing self-channelling and intensity clamping of the driving field. While the later limits the HHG cut-off energy for a given driving field wavelength, self-channelling increases the HHG flux through a longer, phase-matched, interaction length and provides a well-collimated HHG beam covering more than three octaves from <50 to 550 eV.